The Impact of Trade Openness on the Reality Industry in Iraq for the Period (2004-2022) - Ismael Meteab*, Zinah; Faleh Murad , Murad (Journal of Economics and Administrative Sciences, 2024)
Iraq is one of the prominent countries that used to have important industries and enjoyed consumer acceptance, as well as competitiveness and presence in regional and global markets. However, after 2003 and due to trade liberalization, there was a general weakness in the structure of the Iraqi economy. This directly affected the reality of the Iraqi industrial sector, leading to the entry of goods and products from all over the world. With the increase in population and government expenditures, which relied on commodity imports to meet local needs, all aspects of industry in the country were eliminated. The importance of research lies in shedding light on the role of international trade (import and export) in global economies, highlighting the shortcomings in trade policy management, demonstrating the impact of trade openness on the industrial sector's contribution to economic development, and the need for realistic measures to rescue this vital sector from deterioration in Iraq. And the problem of the research is based on the direct negative impact of trade liberalization policy on the reality of the industrial sector in the country. Increased reliance on foreign sources to meet local economic needs is attributed to the deficiencies, backwardness, and stagnation of the production apparatus, rendering it unable to meet total domestic demand. The aim of the research is to shed light on the role of foreign trade in global economies and to clarify the shortcomings in trade policy management, as well as the extent of the impact of trade liberalization on the reality of the industrial sector in achieving economic development. The research found that the industrial sector in Iraq was negatively affected throughout the period (2004-2022) due to the compulsory trade liberalization policy, which led to the shutdown of factories and plants as a result of the low prices of imported goods. Paper type Research paper.